Quality of life assessment in children and their caregivers suffering from allergic rhinitis and/or asthma - Pallavi Wadhawan; Neeraj Gupta; Prakriti Srivastava; Anil Sachdev (Indian Journal of Allergy Asthma and Immunology, 2023)
INTRODUCTION: Asthma and allergic rhinitis (AR) are among the most prevalent diseases worldwide and they frequently persist throughout the life. These have significant effect on physical, financial, and mental wellbeing of patients and caregivers. There have been few attempts previously, assessing the quality of life (QOL) in affected families suffering from these diseases. However, the data from developing countries are scarce. QOL assessment in children and caregivers of patients suffering can help in symptomatic management and provide inputs for the better utilization of resources to achieve optimal treatment. MATERIALS AND METHODS: Patient and caregiver QOLs were ascertained using Mini Pediatric Asthma QOL Questionnaire and Pediatric Asthma Caregiver's QOL Questionnaire, respectively, in the study and correlated with disease severity and chronicity using the parametric and nonparametric statistical tools. RESULTS: There were 246 pairs of children diagnosed with asthma and/or AR and their caregivers attending the pediatric allergy and asthma clinic. Symptom score, emotional domain, and activity limitation in children did not validate a statistically significant difference in QOL in the various grades of AR/asthma/AR with asthma (P = 0.632) (P = 0.772) (P = 0.496) (P = 0.918) (P = 0.384) and (P = 0.561), respectively. In addition, there was no significant correlation between the severity of asthma and caregiver emotional disturbance (P = 0.594) or caregiver activity limitation (P = 0.446). CONCLUSIONS: QOL in children and caregivers where children are suffering from either AR or asthma, or both has not shown any significant difference as per the disease severity or chronicity in various domains. There was no significant difference in QOL noted as per the change in age group, gender of patients, or education status of caregivers.